Identification of plants constituent of conservation forest vegetation Potorono, Sambak, Magelang - Agil, Muhamad; Hidayah, Maulida Ulfa (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2024)
The Potorono Sambak Forest has excellent vegetation and helps to maintain clean water availability for the surrounding community. Various types of plants that grow in the Potorono Forest area of Sambak Village, Magelang have never been identified so their types must be identified. This research aims to identify the various types of plants found in the Potorono Forest Area, Sambak, Magelang to help conservation. The research method used in this study is the exploration method. Every plant found during the exploration of the Potorono Forest area is observed for its morphology, documented, and identified using a plant identification book. The obtained data is then entered into a table based on its categorization and analyzed descriptively qualitatively. The research results obtained as many as 80 species of plants consisting of 26 types of trees, 22 types of shrubs, 20 types of herbs, 5 types of lianas, and 5 types of grass. Of the 80 species, they can be grouped into 47 families with the largest number of Moraceae (6 species), Asteraceae (4 species), and Euphorbiaceae. (4 species). Many types of plants are obtained, and they certainly play an important role in the habitat to maintain the balance of the ecosystem. Therefore, all parties must be actively involved in preserving the Potorono forest ecosystem so that it remains sustainable and beneficial for all living beings.